FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA PADA MATA KULIAH PENGANTAR AKUNTANSI - Adjani, Sagita; Adam, Helmy (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study examined the factors that associated with student performance in introduction of accounting course. Data of this research is taken through the questionnaire. This study received 220 responses of student from 12 college. This research is analyzed by multiple regressions as one of the analysis model. The results indicated that prior knowledge of accounting and motivation are significantly related to student performance in introduction accounting course. Family factor and quality of teaching are not significantly correlated with student performance in introduction of accounting course. This means, internal factor from student are more influence than external factor it self. Â  Â  Keywords: prior knowledge ofaccounting, motivation, family factor, quality of teaching, student performance, introduction of accounting course